A panel of recombinant proteins from human-infective Plasmodium species for serological surveillance - Müller-Sienerth, Nicole (Malar J, 2020)
BACKGROUND: Malaria remains a global health problem and accurate surveillance of Plasmodium parasites that are responsible for this disease is required to guide the most effective distribution of control measures. Serological surveillance will be particularly important in areas of low or periodic transmission because patient antibody responses can provide a measure of historical exposure. While methods for detecting host antibody responses to Plasmodium falciparum and Plasmodium vivax are well established, development of serological assays for Plasmodium knowlesi, Plasmodium ovale and Plasmodium malariae have been inhibited by a lack of immunodiagnostic candidates due to the limited availability of genomic information. METHODS: Using the recently completed genome sequences from P. malariae, P. ovale and P. knowlesi, a set of 33 candidate cell surface and secreted blood-stage antigens was selected and expressed in a recombinant form using a mammalian expression system. These proteins were added to an existing panel of antigens from P. falciparum and P. vivax and the immunoreactivity of IgG, IgM and IgA immunoglobulins from individuals diagnosed with infections to each of the five different Plasmodium species was evaluated by ELISA. Logistic regression modelling was used to quantify the ability of the responses to determine prior exposure to the different Plasmodium species. RESULTS: Using sera from European travellers with diagnosed Plasmodium infections, antigens showing species-specific immunoreactivity were identified to select a panel of 22 proteins from five Plasmodium species for serological profiling. The immunoreactivity to the antigens in the panel of sera taken from travellers and individuals living in malaria-endemic regions with diagnosed infections showed moderate power to predict infections by each species, including P. ovale, P. malariae and P. knowlesi. Using a larger set of patient samples and logistic regression modelling it was shown that exposure to P. knowlesi could be accurately detected (AUC = 91%) using an antigen panel consisting of the P. knowlesi orthologues of MSP10, P12 and P38. CONCLUSIONS: Using the recent availability of genome sequences to all human-infective Plasmodium spp. parasites and a method of expressing Plasmodium proteins in a secreted functional form, an antigen panel has been compiled that will be useful to determine exposure to these parasites.